Treating the Troops - Howe, Edmund G. (The Hastings Center report, 1991)
As we go to press, the threat of biological or chemical warfare in the Persian Gulf is no longer imminent. Yet the questions raised by the proposed use of “investigational drugs,” without informed consent, to protect U.S. troops remain. The article by Edmund G. Howe and Edward D. Martin presents the arguments that informed the Pentagon's thinking on the subject. It and the commentaries, by George J. Annas and Michael A. Grodin, and Robert J. Levine, explore, among others, issues of informed consent, of distinguishing ‘research’ and ‘treatment,’ and of the nature and extent of the autonomy of military personnel.—B-JC, HLN.